The Status of Using Blended Learning in Teaching the English Language at the Primary Stage from Teachers’ Point of View - Samawi, Rania Ratib (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the degree of using blended learning in the teaching English language at the primary stage from teachers’ point of view. The researcher followed the analytical descriptive approach, which is compatible with the variables and objective of the study. The questionnaire was used as a tool to collect information after making sure of its validity and reliability. The sample was selected using random sampling method. The number of the sample was (109) male and female teachers. The results of the study showed that the degree of using blended learning in teaching English at the primary stage from the teachers' point of view was "moderate" and the average of the use of reality as a whole was (3.14). The obstacles facing English language teachers of Ain Al-Basha schools regarding using blended learning in teaching English are mostly represented in the lack of training courses related to blended learning.
Keywords: Blended Learning; English Language; Primary Stage